A functional IL1RL1 variant regulates corticosteroid-induced sST2 expression in ulcerative colitis - Díaz-Jiménez, David (Sci Rep, 2017)
The ST2/IL33 signalling pathway has been associated with ulcerative colitis (UC). ST2, encoded by the IL1RL1 gene, is expressed as both a membrane-anchored receptor (ST2L) activated by IL33 and as a soluble receptor (sST2) with anti-inflammatory properties. In UC patients, sST2 is further increased by corticosteroid treatment; however, the glucocorticoid-mediated molecular regulation remains unknown. We therefore tested whether genetic variants in the IL1RL1 distal promoter are involved in UC and affect glucocorticoid-mediated ST2 expression. Serum ST2 levels and genetic variants in the IL1RL1 distal promoter were examined by ELISA and PCR sequencing in UC patients receiving corticosteroids. Glucocorticoid-mediated ST2 production was evaluated in intestinal mucosa cultures. Molecular regulation of glucocorticoid-mediated ST2 was assessed by RT-qPCR, ChIP assay and luciferase reporter assay. Dexamethasone effect on ST2 transcript expression was analyzed in leukocytes and related to IL1RL1 variants. Sequencing of a distal IL1RL1 promoter region demonstrated that SNPs rs6543115(C) and rs6543116(A) are associated with increased sST2 in UC patients on corticosteroids. Dexamethasone up-regulated sST2 transcription through interaction with the glucocorticoid-response element (GRE) carrying rs6543115(C) variant. Our data indicate that IL1RL1 SNPs rs6543115(C) confer susceptibility to UC and is contained in the GRE, which may modulate glucocorticoid-induced sST2 expression.